PERANCANGAN INFOGRAFIS UNTUK PENYAMPAIAN INFORMASI MENGENAI SOCIAL ANXIETY DISORDER - Setiawan, Ade; Arief, Lukman (Anggada : Jurnal Desain dan Seni, 2021)
Social anxiety disorder can wreak havoc on the lives of people suffering from this condition. Individuals who have social anxiety disorder, or social phobia, may have very limited social or romantic relationships, leaving them feeling helpless, lonely, or even isolated. The purpose of this design is to provide information about social anxiety disorder, from understanding to how to overcome it. The design stage includes data collection, conceptual work, and design creation. The data collection process is obtained from literature studies and documentation of related information about social anxiety disorder which will later be used at the design stage of the infographic work.